Pengaruh deregulasi moneter terhadap likuiditas perekonomian Indonesia: Studi empiris model koreksi kesalahan - Samsubar Saleh; Samsul Hidayat (Universitas Islam Indonesia, 2000)
Since monetary deregulation in decade 1980, financial and monetary sector in Indonesia change. The monetary deregulation package affects much to liquidity. This paper evaluates the impact of monetary deregulation to broad money (M2) by using Error Correlation Model (ECM).